La sombra de la muerte: Un estudio de mitología comparada entre México y China. - Li, Ya (Confluencia: Revista Hispánica de Cultura y Literatura)
The article focuses on a comparative study of the mythology related to death between the Aztec civilization of Mexico and the Huaxia civilization of China, the predecessor of the Han ethnicity. It analyzes how both cultures conceive the creation of the world, death as transformation, and sacrifice as a regenerating act, highlighting similarities in the cosmogonic structure and differences in the relationship between humans and deities. While in Chinese mythology the gods are close and benevolent figures who promote human action to overcome catastrophes, in the Mexica tradition the deities are omnipotent and humanity depends on their will, emphasizing obedience and sacrifice. The study concludes that, despite their differences, both traditions share the vision of death as a process of cosmic and social renewal, where voluntary sacrifice is fundamental for the continuity of life and the universal order.